An in-situ versatile screening method for identifying SVOC sources in indoor environments - Li, Yatai; Zhang, Shihao; Guo, Zichen; Wang, Lixin; Lin Qiao; Yu Chen; Fan, Guangtao; Sun, Chanjuan; Sun, Yuexia; Liu, YingJun; Deng, Qihong (Environment International, 2024)
Indoor semivolatile organic compounds (SVOCs) pose a substantial threat to human health. However, identifying the sources of these emissions has been challenging owing to the scarcity of convenient and practical on-site methodologies. Herein, a novel method for source screening was proposed using aluminum silicate sampling strips to adsorb SVOCs from the surface air of indoor materials. The adsorbed SVOC levels indicate the emission intensity of these materials into indoor environments. Additionally, compact sampling strips can be readily fixed to any vertical surface using a static sticker, facilitating the characterization of various materials in practical settings. Laboratory-simulated experiments demonstrated the capability of the proposed method to differentiate between source and non-source materials within a 10-cm distance in the same space. In practical scenarios, the primary emission sources identified via this method exhibited a consistent correlation with the contents of the corresponding materials obtained from the traditional solvent-extraction method. As the adsorbed SVOCs were directly transferred to a GC–MS through thermal desorption instead of the solvent-extraction procedure, the proposed method demonstrated several-fold improvements in analytical sensitivity and efficiency. Using this versatile screening technique, some emerging and important SVOC species were identified within specific indoor materials. Eliminating these sources has been demonstrated as an effective approach to mitigate SVOC pollution. Overall, the proposed method offers a powerful tool for managing indoor pollutants and safeguarding human health.
Keywords: Indoor pollution; Pollution control; Routine monitoring; Source screening; SVOC